2013
DOI: 10.1007/s40435-013-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of dipteran flight mechanism

Abstract: In this paper, a novel model for the mechanism of dipteran flight motor is proposed and a flight dynamics is explored by nonlinear dynamics techniques. This model comprises a lumped mass, a pair of inclined rigid bars and a pair of horizontal springs. Even the springs are linear, this system is irrationally nonlinear which causes difficulty for classical nonlinear analysis. We investigate the original irrational equation by direct numerical simulation avoiding Taylor's expansion to retain the intrinsic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…An experimental prototype is built to demonstrate the unique dynamic characteristics of the ZS system based upon the schematic shown in Fig. 3(a), which with the trajectory S of point P is an ellipse, which can be regarded as the coupling of a positive and a negative stiffness components 30,40,41 . The prototype with the adjustable loading 27kg ≤ M + m ≤ 37kg, the total stiffness of the vertical springs k 0 = 1.04N/mm, the total stiffness of the horizontal springs k/4 = 1N/mm, maximum stroke l 0 = R x = 200mm, minimum pre-stretch of horizontal springs B = 0mm, and the semi-minor axis R y = 102mm.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…An experimental prototype is built to demonstrate the unique dynamic characteristics of the ZS system based upon the schematic shown in Fig. 3(a), which with the trajectory S of point P is an ellipse, which can be regarded as the coupling of a positive and a negative stiffness components 30,40,41 . The prototype with the adjustable loading 27kg ≤ M + m ≤ 37kg, the total stiffness of the vertical springs k 0 = 1.04N/mm, the total stiffness of the horizontal springs k/4 = 1N/mm, maximum stroke l 0 = R x = 200mm, minimum pre-stretch of horizontal springs B = 0mm, and the semi-minor axis R y = 102mm.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Write the dimensionless dynamic Eq. ( 9) into the form of two simultaneous first-order differential equations in horizontal and vertical directions, obtained by (10) and (11) separately, (8) The phase diagrams of the non-conservative autonomous systems are shown in Fig. 4.…”
Section: Sqzs Analysismentioning
confidence: 99%
“…Traditional scheme is mainly based on the linear theory to separate the structure from the basement [5][6][7][8][9][10], which is just effective for high-frequency waves. Recently, attentions have been made on nonlinear lowfrequency vibration isolation structure, which significantly improves the isolation performance [11][12][13][14][15][16]. However, these works mainly focus on vertical damage using stable quasi-zero stiffness (SQZS) system with single degree-of-freedom (DOF), which is invalid for horizontal direction.…”
Section: Introductionmentioning
confidence: 99%
“…These elements, usually referred to as Quasi-Zero-Stiffness (QZS) mechanisms [5] or Negative Stiffness Mechanisms (NSM) [6], can generate a negative restoring force or negative stiffness so that low dynamic stiffness of the overall system is achieved while keeping its static stiffness high and the static deflection small. Such mechanisms are often created by springs [7][8][9][10], magnets [11,12], bars [13,14], circular rings [15], or composite plates [16]. By transforming a linear system into a nonlinear system with NSMs, it has been shown that the natural frequency of the linearized system can be reduced.…”
Section: Introductionmentioning
confidence: 99%